Administrative Monetary Penalties for Non-Compliance with Sanitary Restrictions from The Perspective of Polish Constitutional Law - Pawel NOWOTKO (Communications of International Proceedings, 2021)
This paper examines whether the legal bases for imposing administrative monetary penalties for non-compliance with sanitary restrictions related to the COVID-19 epidemic existing in the Polish legal system conform to the principle of a democratic state of law. The issue is analyzed from the angle of specific principles derived from the principle of a democratic state of law. Bearing in mind the extraordinary nature of the actual situation in which the legal regulations under examination were introduced, the author shows that these regulations do not meet the requirements implied by the principle of a democratic state ruled by law. He points out that the Polish Constitution provides relevant solutions in case ordinary constitutional measures are not sufficient, but the solutions have not been applied for no sound reason. In his analysis, the author refers to relevant legislative acts and legal literature.
Keywords: Constitutional law; administrative penalties; principle of a democratic state ruled by law; pandemic; COVID-19